(untitled) (The Agriculturists, 2013)
Four orange fleshed sweet potato (OFSP) genotypes viz., CIP 194513.15, CIP 194515.15, CIP 441132 and CIP 440267.2 collected from International Potato Centre (CIP) and four BARI (Bangladesh Agricultural Research Institute) - hybrid orange flesh sweet potato genotypes viz., H16/06, H19/06, H3/07 and H6/07 were evaluated against BARI SP-3 and BARI SP-4 having orange fleshed at Agricultural Research Station, Bangladesh Agricultural Research Institute, Pahartali, Chittagong for yield and quality. The highest (31.59 t/ha) tuberous root yield was found in CIP 194513.15 which was followed by CIP 440267.2 (30.97 t/ha) and the lowest yield (13.34 t/ha) was obtained in BARI SP 3. The maximum dry matter (29.83%) was obtained in H6/07 while the minimum dry matter (17.61%) was obtained in CIP 441132. Among the tested genotypes the highest (approximately) Vitamin A (919.2 ?g/100 g RE, FW) was recorded in CIP 440267.2, which had red skin and latex absent flesh and the lowest was (approximately) in H6/07 (Vit A 0.0 ?g/100 g RE, FW). The results of the present study indicated that CIP 440267.2 is suitable among the OFSP genotypes for cultivation in Bangladesh on the basis of yield and quality mainly carotinous. DOI: http://dx.doi.org/10.3329/agric.v11i2.17483 The Agriculturists 2013; 11(2) 21-27